Novel development of carbonate apatite-chitosan scaffolds based on lyophilization technique for bone tissue engineering - Maretaningtias Dwi Ariani (Dental Journal (Majalah Kedokteran Gigi), 2012)
Background: The natural biopolymer chitosan (Ch) is currently regarded as a candidate for bone tissue engineering. However, Ch is poor for cell adhesion and low bone formation ability. In order to enhance cell adhesion and bone formation ability, combination of Ch with carbonate apatite (CA) was developed. Purpose: The aim of this study was to make carbonate apatite-chitosan scaffolds (CAChSs) and evaluate its osteoconductivity in terms of cell proliferation. Methods: Chitosan scaffolds (ChSs) were made by the following procedure. Twenty-five, 50, 100, 200 and 400 mg Ch was dissolved into 5 ml of 2% acetic acid (CH3COOH), shaked for 15 min and neutralized with 15 ml of 0.1 M sodium hydroxide (NaOH) solution. After centrifugation, Ch gel was packed into the molds then frozen at -80°C for 2h and dried in a freeze dry machine for 24h. The sponges were subjected to UV radiation for 2h. To make CA-ChSs, 200 mg Ch was selected. After neutralization, 50 mg of 0.06 M CA were added into the 200 mg Ch gel. The structure of CA-ChSs was observed by scanning electron microscope (SEM). Mouse osteoblast-like cell (MC3T3-E1) proliferation in these scaffolds was investigated at 1, 7, 14 and 21 days. Results: Three dimensional porous structures of CA-ChSs were clearly observed by SEM. Proliferated cell numbers in CA-ChSs was significantly higher than those in ChSs (control) at each stage (p<0.05). Conclusion: It can be concluded that newly developed CA-ChSs had three-dimensional interconnected porous structure, good handling property and supporting ability of proliferation of osteoblasts. It is suggested that newly developed CA-ChSs could be considered as a scaffolds material for bone tissue enginearing.Latar belakang: Kitosan yang merupakan biopolimer alami dianggap sebagai salah satu kandidat untuk rekayasa jaringan tulang. Namun, kitosan memiliki kelemahan terhadap adhesi sel dan kurang mampu membentuk tulang yang cukup. Untuk meningkatkan adhesi sel dan kemampuan pembentukan tulang, telah dikembangkan suatu scaffolds yang menggabungkan kitosan dengan carbonate apatite (CA). Tujuan: Penelitian ini bertujuan untuk membuat carbonate apatite-chitosan scaffolds (CA-ChSs) serta mengevaluasi osteokonduktivitas CA-ChSs dari sudut pandang proliferasi sel. Metode: Chitosan scaffolds (ChSs) dibuat dengan prosedur berikut ini. Dua puluh lima, 50, 100, 200 dan 400 mg bubuk kitosan dilarutkan dalam 5 ml asam asetat (CH3COOH) 2%, dikocok selama 15 menit dan dinetralkan dengan 15 ml 0,1 M larutan sodium hidroksia (NaOH). Setelah sentrifugasi, gel kitosan dikemas ke dalam cetakan teflon kemudian dibekukan pada suhu -80°C selama 2 jam dan dikeringkan dalam mesin beku kering pada suhu -54°C selama 24 jam. Selanjutnya dilakukan radiasi ultraviolet pada ChSs selama 2 jam. Untuk membuat CA-ChSs, dipilih ChSs yang berisi 200 mg bubuk kitosan. Setelah dinetralisir, 50 mg dari 0.06 M CA ditambahkan ke dalam kitosan gel yang berisi 200 mg bubuk kitosan. Struktur CA-ChSs diamati dengan scanning electron microscope (SEM). Proliferasi mouse osteoblast-like cell (MC3T3-E1) dalam ChSs dan CA-ChSs dievaluasi pada hari ke-1, 7 dan 14. Hasil: CA-ChSs dengan struktur tiga dimensi yang berpori dapat diamati dengan jelas menggunakan SEM. Jumlah pertumbuhan dan perkembangan sel pada CA-ChSs secara signifikan lebih banyak dibandingkan pada ChSs (kontrol) pada setiap tahap pengamatan di hari ke-1, 7, 14 dan 21 (p<0.05). Kesimpulan: Dapat disimpulkan bahwa CA-ChSs mempunyai struktur tiga dimensi dengan pori-pori yang saling berhubungan satu sama lain dan dapat meningkatkan proliferasi osteoblast. Hal ini menunjukkan bahwa CA-ChSs adalah kandidat untuk rekayasa jaringan tulang.